Full-Duplex Amplify-and-Forward MIMO Relaying: Design and Performance Analysis Under Erroneous CSI and Hardware Impairments - Omid Taghizadeh; Slawomir Stanczak; Hiroki Iimori; Giuseppe Thadeu Freitas De Abreu (IEEE Open Journal of the Communications Society, 2021)
Full-duplex amplify-and-forward multiple-input multiple-output relaying has been the focus of several recent studies, due to the potential for achieving a higher spectral efficiency and lower latency, together with inherent processing simplicity. However, when the impact of hardware distortions are considered, such relays suffer from a distortion-amplification loop, due to the inter-dependent nature of the relay transmit signal covariance and the residual self-interference covariance. The aforementioned behavior leads to a significant performance degradation for a system with a low or medium hardware accuracy. In this work, we analyze the relay transfer function as well as the mean squared-error performance of a full-duplex amplify-and-forward multiple-input multiple-output relaying communication, under the impact of collective sources of additive and multiplicative transmit and receive impairments. Building on the performed analysis, an optimization problem is devised to minimize the communication Mean Squared-Error and solved by employing the recently proposed penalty dual-decomposition framework. The proposed solution converges to a stationary point of the original problem via a sequence of convex quadratic programs, thereby enjoying an acceptable arithmetic complexity as the problem dimensions grow large. Numerical simulations verify the significance of the proposed distortion-aware design and analysis, compared to the common simplified approaches, as the hardware accuracy degrades.